Lacan and the subject of law toward a psychoanalytic critical legal theory - Caudill, David Stanley 1952- (Humanities Press, 1997)
Application of Lacan's theory to some concrete legal problems follows in the second part of the book with a series of studies including child abuse hysteria, land use debates, the critique of legal ideology; and religion in law and politics
Keywords: Lacan, Jacques <1901-1981> - Et le droit; Lacan, Jacques <1901-1981>; Lacan, Jacques -- 1901-1981; Critique du droit; Psychanalyse et droit; Psychoanalytische interpretatie; Rechtstheorie; Recht; Critical legal studies; Law -- Methodology; Psychoanalytic interpretation; Sociological jurisprudence; Psychoanalyse